Rancang Bangun Sistem Pendukung Keputusan untuk Pemilihan Tema Tugas Akhir Mahasiswa Manajemen Informatika Universitas Merdeka Madiun - Alexander Kenzy Pinaring Gusti; Pradityo Utomo; Sukadi (MEKAR : Journal Information System and Computer Application, 2025)
Abstract: - Students in the Informatics Management Study Program at Universitas Merdeka Madiun must complete a Final Project (TA) as part of their graduation requirements. However, choosing a project topic that matches their interests and abilities can be difficult. To help solve this problem, a web-based Decision Support System (DSS) was developed using the Weighted Sum Model (WSM). This study focuses on designing and developing a system to assist students in selecting appropriate final project topics more efficiently and objectively. The WSM method is used to assess several theme options based on a set of established criteria. The system was built using the Waterfall development model, which involves analysis, design, implementation, testing, and maintenance stages. Black Box Testing was conducted to verify the system's functionality. The application supports two user roles: administrators and students. Administrators manage the system’s data, including criteria, theme options, evaluations, and user accounts. Students can view recommended project topics and update their profiles. Testing showed a 100% success rate, indicating the system’s reliability. By using this DSS, students can make more informed decisions about their final project themes, improving both the selection process and the overall quality of their research through the use of educational technology.